Philanthropy in Majelis Taklim as Contesting Space: Between Women’s Subjectivities and Islamist Movement in Surakarta - Okta Nurul Hidayati; Irhas Badruzaman (DINIKA : Academic Journal of Islamic Studies, 2022)
This study examines the response of the women’s majelis taklimin Surakarta to the Islamist movement, through philanthropic activities.This study is focused on interviewing the congregations and the administrators of three majelis taklim-Al Husna, Humaira, and Da'wah Squad. I argue that majelis taklimis a space to express women’s subjectivities and pieties. This study shows that there are divided philanthropic activities at the group and individual level.At the group (majelis) level, especially at Al Husna, there is a potential for expansion of the Islamist movement proven by their support of the Islamist group's philanthropy. Da'wah Squad and Humaira shows a different response in limiting Islamism by organizing independent and creative philanthropy that targets wider beneficiaries. At the individual level, some administrators and congregations of the three majelis have shown their potential for narrowing the Islamist movement with different variations. This research contributes to presenting the women’s philanthropy within women’s piety movement in the context of emerging Islamism in Surakarta.